PKM pada Masyarakat Kelurahan Jagakarsa Jakarta Selatan - Deni Nasir Ahmad; Rahmatulloh Rahmatulloh; Mamiek Suendartie (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
The aim of the activity is information on waste management and waste management practice activities to reduce the impact caused by waste based on Regional Regulation Number 3 of 2013 concerning Waste Management. The service method used: 1. Direct observation, namely the service member comes directly to the service location to collect data. We do this before and during the activity. 2. Carrying out environmental improvement project planning activities where we divide the team into several tasks and activities, namely, the first step is providing education regarding waste management legislation in the DKI Jakarta Provincial Government area and the impact of waste on the living environment, the second step is providing training in making technology household waste management. 3. Conduct joint evaluations and sharing to find mutual agreement in making environmental improvements. Results of community service activities Community service activities were carried out on Saturdays and Sundays, from March 14 2020 to March 15 2020 at 09.00 to 13.00 WIB located in the Jagakarsa sub-district area in several Jagakarsa sub-districts, South Jakarta. This community service activity was carried out to provide information regarding Waste Management in the DKI South Jakarta Region regarding the Implementation of Regional Regulation Number 4 of 2019, Amendments to Regional Regulation Number 3 of 2013 concerning Waste Management. Conclusion The training participants were very enthusiastic and proactive in all activities from the beginning to the end of the activity, it was proven that the many questions were mutually constructive in order to improve the environment for the better and maximize waste as a valuable value that can be used in society as economic value for the community.